Spermine-Related DNA Hypermethylation and Elevated Expression of Genes for Collagen Formation are Susceptible Factors for Chemotherapy-Induced Hand-Foot Syndrome in Chinese Colorectal Cancer Patients - Mingming Li; Jiani Chen; Shaoqun Liu; Xiaomeng Sun; Huilin Xu; Qianmin Gao; Xintao Chen; Chaowen Xi; Doudou Huang; Yi Deng; Feng Zhang; Shouhong Gao; et al. (Frontiers Media S.A., 2021)
Hand-foot syndrome (HFS) is a common capecitabine-based chemotherapy-related adverse event (CRAE) in patients with colorectal cancer (CRC). It is of great significance to comprehensively identify susceptible factors for HFS, and further to elucidate the biomolecular mechanism of HFS susceptibility. We performed an untargeted multi-omics analysis integrating DNA methylation, transcriptome, and metabolome data of 63 Chinese CRC patients who had complete CRAE records during capecitabine-based chemotherapy. We found that the metabolome changes for each of matched plasma, urine, and normal colorectal tissue (CRT) in relation to HFS were characterized by chronic tissue damage, which was indicated by reduced nucleotide salvage, elevated spermine level, and increased production of endogenous cytotoxic metabolites. HFS-related transcriptome changes of CRT showed an overall suppressed inflammation profile but increased M2 macrophage polarization. HFS-related DNA methylation of CRT presented gene-specific hypermethylation on genes mainly for collagen formation. The hypermethylation was accumulated in the opensea and shore regions, which elicited a positive effect on gene expression. Additionally, we developed and validated models combining relevant biomarkers showing reasonably good discrimination performance with the area under the receiver operating characteristic curve values from 0.833 to 0.955. Our results demonstrated that the multi-omics variations associated with a profibrotic phenotype were closely related to HFS susceptibility. HFS-related biomolecular variations in CRT contributed more to the relevant biomolecular mechanism of HFS than in plasma and urine. Spermine-related DNA hypermethylation and elevated expression of genes for collagen formation were closely associated with HFS susceptibility. These findings provided new insights into the susceptible factors for chemotherapy-induced HFS, which can promote the implementation of individualized treatment against HFS.